Harnessing green human capital and circular economy in urbanization: Advancing water resilience through resource conservation and green technology - Nieke Masruchiyah; Novita Damayanti; Prasetya Yoga Santoso; Asep Marfu (Environmental Challenges)
This study investigates the interplay between green human capital (GHC), circular economy practices, and green technology adoption in strengthening urban water resilience in Indonesia. Using PLS-SEM, IPMA, and predictive performance analysis, the research examines how these factors influence resource conservation and sustainable urban water management. Data were collected from urban planners and policymakers. Findings show that GHC significantly promotes resource conservation and technology adoption, while circular economy practices enhance sustainability through waste reduction and resource reuse. Resource conservation mediates the relationship between key constructs and urban water resilience. The study contributes to the literature by offering empirical insights into the integrated role of human, technological, and systemic factors in urban water resilience. It recommends that planners prioritize GHC development, support circular economy models, and incentivize green technologies through integrated policy frameworks.